Do cognitive, language, or physical impairments affect participation in a trial of self-management programs for stroke?. Issue 1 (January 2016) - Cadilhac, Dominique A; Kilkenny, Monique F; Srikanth, Velandai; Lindley, Richard I; Lalor, Erin; Osborne, Richard H; Batterbsy, Malcolm
Background: Research studies may have limited generalizability when survivors of stroke with physical, language, or cognitive impairments are excluded. Aims: To assess whether presence of cognitive, language, or global impairments affects participation in self-management programs. Methods: Stroke survivors were recruited in South Australia from seven hospitals or via advertisements into a randomized controlled trial (1:1:1 ratio) of a Stroke Self-Management Program, the Stanford chronic condition self-management program, or standard care. Impairment status was measured using: Cognistat (cognition), Frenchay Aphasia assessment (language), modified Rankin Score (mRS; where score 3–5 = global disability). Primary outcomes: participation (i.e. booked, accessed, and completed a program (defined as attending ≥ 50% of sessions)) and safety (i.e. adverse events). Outcomes were compared by impairment status. Results: Among 315 people screened 143/149 eligible were randomized (median age 71 years; 41% male; with impairments: 62% cognitive, 34% language, 64% global disability). Participation did not differ by cognitive or language impairment status (cognitive 75%, no cognitive 68%, p = 0.54; language 78%, no language 69%, p = 0.42). However, participation did vary by global impairment status (global disability 61%, no disability 96%, p < 0.001). Participants with cognitive impairment experienced more adverse events (severe n = 9 versus no cognitive impairment n = 1). Conclusion: Survivors of stroke with cognitive, language, or global impairments are able to participate in self-management programs and should be included in these types of research studies or programs. Reduced participation by those with global disability and the possibility of more adverse events in people with cognitive impairments needs to be considered.